Knowledge of and Compliance With Pitch Count Recommendations: A Survey of Youth Baseball Coaches - Fazarale, Joseph J. (SAGE Publications, 2012)
BACKGROUND: Pain and injuries suffered by youth pitchers are ongoing concerns that have been addressed through the institution of rules and recommendations regarding pitch counts and rest periods. The aim of our study was to see if coaches of youth baseball pitchers in our region were aware of the recommended guidelines and if they followed them. METHODS: An Internet-based survey consisting of 18 items including demographic information and questions concerning the USA Baseball Medical and Safety Advisory Committee pitching guidelines was sent to coaches affiliated with a local youth league to assess their knowledge of and reported compliance with these recommendations. RESULTS: Ninety-five of 228 coaches (41.4%) participated in the survey. On average, coaches answered 43% of questions regarding pitch count and rest periods correctly; 73% reported that they followed the recommendations, while only 53% felt that other coaches in the league abided by the recommendations. Thirty-five percent of coaches stated that their pitchers reported shoulder or elbow pain during the season, and 19% reported that one of their pitchers pitched a game with a sore or fatigued arm during the season. No coaches reported any pitching-related injuries among their players requiring surgery. Fewer than 10% of coaches reported that their players pitched in multiple leagues or participated in showcases, while 91% reported that pitchers attended camps or received specific instruction to improve their pitching form. CONCLUSIONS: This study shows that this subset of youth baseball coaches is deficient with regard to knowledge of the USA Baseball Medical and Safety Advisory Committee pitching guidelines. This situation may put youth pitchers at increased risk for upper extremity pain and injuries.